COMPARATIVE ANALYSIS OF STRUCTURES WITH IMPERSONAL MEANING IN THE SPANISH LANGUAGE AND IMPERSONAL STRUCTURES IN THE FRENCH LANGUAGE - Robertovna Gozalova, Marina; Igorevna Makarova, Aleksandra; Evgenievna Zaitseva, Olga; Yurievna Sokolova, Elena (Revista Inclusiones, 2019)
In this article, the authors comprehensively analyze the ways of expressing impersonality in the Spanish language and determine the principal similarities and differences between structures with impersonal meaning in the two closely related languages: French and Spanish. There is a number of difficult theoretical issues connected to the analysis of impersonality in the Spanish language: active and passive elements in the meaning of the verb, the role of the pronominal verb form, the notion of indefinite personal and impersonal structures, the role of the pronoun uno, semantic features of infinitive and gerund usage.